FRI0260 Quantitative CT Indexes in ILD-SSC Patients with Different Autoantibodies. (15th July 2016) - Ariani, A.; Bravi, E.; Saracco, M.; Parisi, S.; De Gennaro, F.; Idolazzi, L.; Silva, M.; Seletti, V.; Lumetti, F.; Caramaschi, P.; Benini, C.; Bodini, F.C.; et al.
Abstract : Background: Quantitative Computed Tomography (QCT) is an innovative method to assess the severity of interstitial lung disease (ILD) related to systemic sclerosis (SSc). QCT is correlated to semi-quantitative radiological scores (SQs) and functional outcomes (e.g. FVC, DLco, oxygen desaturation after exercise) in SSc patients. However, the autoimmune profile can deeply influence the respiratory system's involvement. Objectives: The main aim of this study is to verify the correlation between SQs, FVC, DLco and QCT in SSc patients clustered according to their autoimmunity. Methods: Three hundred three (303) SSc patients were enrolled and underwent functional and radiological assessment. Chest CTs of each patient were evaluated with both SQs and Horos (a software up to perform voxel-wise analysis) in order to obtain QCT indexes. Results: Patients were divided in three groups (94 with ACA, 93 with antiScl70, 116 with other autoantibodies). QCT indexes taken into account were kurtosis (Kurt), skewness (Skew), Standard Deviation (SDev), Mean Lung Attenuation (MLA) and fibrosis ratio (FR). Except for the last one, all QCT indexes were assessed both in the parenchymal (pQCT) and in the whole lung (tQCT). The statistically significant (p<0, 05) correlation coefficients between SQs, FVC and DLco vs QCT are listed in Table 1 . In ACA patients there are not correlations between DLco and QCT indexes. Conclusions: Our results confirm that the majority of QCT indexes are correlated to SQS and functional outcomes. The strongest correlation coefficients were in the antiScl70 subgroup while the weakest ones were in ACA patients. This relevant difference, possibly due to the different prevalence of ILD and type of lung involvement in these two subgroups, should be taken into account when applying the QCT assessment to SSc patients. Disclosure of Interest: None declared